Homemade Fenestrated Stent-Grafts for Complete Endovascular Repair of Aortic Arch Dissections. (October 2019) - Canaud, Ludovic; Ozdemir, Baris Ata; Chassin-Trubert, Lucien; Sfeir, Julien; Alric, Pierre; Gandet, Thomas
Purpose: To evaluate outcomes of homemade fenestrated stent-grafts for complete endovascular aortic repair of aortic arch dissections.Materials and Methods: From July 2014 through September 2018, 35 patients (mean age 66±11 years; 25 men) underwent homemade fenestrated stent-graft repair of acute (n=16) or chronic (n=10) complicated type B aortic dissections (n=16) and dissecting aortic arch aneurysms subsequent to surgical treatment of acute type A dissections (n=9). Nineteen (54%) procedures were emergent.Results: Zone 2 single-fenestrated stent-grafts were used in 25 cases; the remaining 10 were double-fenestrated stent-grafts deployed in zone 0. Median time for stent-graft modification was 18 minutes (range 16–20). Technical success was achieved in all cases. An immediate distal type I endoleak was treated intraoperatively. Among the double-fenestrated stent-graft cases, the left subclavian artery fenestration could not be cannulated in 2 patients and revascularization was required. Partial coverage of the left common carotid artery necessitated placement of a covered stent in 3 cases. One (3%) patient had a stroke without permanent sequelae. Two type II endoleaks required additional covered stent placement at 5 and 7 days postoperatively, respectively. The 30-day mortality was 6% (2 patients with ruptured aortic arch aneurysm). During a mean follow-up of 17.6±13 months, there was no aortic rupture or retrograde dissection. One late type I endoleak was treated with additional proximal fenestrated stent-graft placement. One type II endoleak is currently under observation. One additional patient died (unrelated to the aorta); overall mortality was 9%. All supra-aortic trunks were patent.Conclusion: The use of homemade fenestrated stent-grafts for endovascular repair of aortic arch dissections is feasible and effective for total endovascular aortic arch repair. Durability concerns will need to be assessed in additional studies with long-term follow-up.